A longitudinal investigation of children’s trauma memory characteristics and their relationship with posttraumatic stress disorder symptoms - McGuire, R; Hiller, RM; Ehlers, A; Fearon, P; Meiser-Stedman, R; Leuteritz, S; Halligan, SL (Springer Nature, 2021)
While trauma memory characteristics are considered a core predictor of adult PTSD, the literature on child PTSD is limited and inconsistent. We investigated whether children’s trauma memory characteristics predict their posttraumatic stress symptoms (PTSS) at 1 month and 6 months post-trauma. We recruited 126 6–13 year olds who experienced a single-incident trauma that led to attendance at an emergency department. We assessed trauma memory disorganisation and sensory-emotional qualities through both narrative recall and self-report questionnaire, and PTSS at 1-month post-trauma and at 6-month follow-up. We found that, after controlling for age, children’s self-reported trauma memory characteristics were positively associated with their concurrent PTSS, and longitudinally predicted symptoms 6-months later. However, observable trauma memory characteristics coded from children’s narratives were not related to PTSS at any time. This suggests that children’s perceptions of their trauma memories are a more reliable predictor of the development and maintenance of PTSS than the nature of their trauma narrative, which has important implications for clinical practice.